Reflections on “Centralization and the Civil Administrative Division” in the Nation-State Building Process during the Early Period of the Republic - Barış Kandeğer (Siyasal: Journal of Political Sciences)
The founders of the Turkish Republic had in mind the idea and aim of building a modern nation-state and society. This idea and aim formed the basis of the approaches and policies adopted in the early period of the Republic. This paper aims to seek an answer to the question of whether there is a close relationship and a multidimensional interaction between nation-state building, centralization and administrative division in the early Republican period. The paper argues that the centralization approach and civil administrative division had multidimensional functions beyond the administrative function “for the construction of the nation-state in the early Republican period”. In this context, parliamentary debates, laws, draft laws and legal texts on the centralization and civil administrative division served as the main sources of reference and were analyzed as part of the study. In this framework, the basic approaches and policies adopted in the nation-state-building process of the early Republican period are presented, followed by an analysis of the role and functions of the laws and draft laws that constitute the basis for the centralization and civil administrative division in the construction of the identity of the “modern nation-state” in the light of parliamentary debates. The paper also draws attention to the conclusion that the founders of the Republic were engaged in a decentralist discourse and centralist action in the aforementioned construction process and that they adopted the centralization and civil administrative division as a constructive approach for the modern nation-state and society.